Copper zinc tin sulfide-based thin film solar cells - Ito, Kentaro (Chichester : Wiley, 2014)
Beginning with an overview and historical background of Copper Zinc Tin Sulphide (CZTS) technology, subsequent chapters cover properties of CZTS thin films, different preparation methods of CZTS thin films, a comparative study of CZTS and CIGS solar cell, computational approach, and future applications of CZTS thin film solar modules to both ground-mount and rooftop installation. The semiconducting compound (CZTS) is made up earth-abundant, low-cost and non-toxic elements, which make it an ideal candidate to replace Cu(In, Ga)Se2 (CIGS) and CdTe solar cells which face material scarcity and toxic.
9.3 Properties of Sputtered Precursors9.4 Annealing of Sputtered Precursors; 9.5 Device Performance; 9.6 Summary; References; Chapter 10 Coevaporation of CZTS Films and Solar Cells; 10.1 Introduction; 10.2 Basic Principles; 10.3 Process Variations; Acknowledgements; References; Chapter 11 Synthesis of CZTSSe Thin Films from Nanocrystal Inks; 11.1 Introduction; 11.2 Nanocrystal Synthesis; 11.3 Nanocrystal Characterization; 11.4 Sintering; 11.5 Conclusion; References; Chapter 12 CZTS Thin Films Prepared by a Non-Vacuum Process; 12.1 Introduction; 12.2 Sol-Gel Sulfurization Method.
12.3 Preparation of CZTS Thin Films by Sol-Gel Sulfurization Method.
Includes bibliographical references and index.
Print version record.
Keywords: Photovoltaic cells -- Materials; Solar cells -- Materials; Copper-zinc alloys; Copper-zinc alloys; Photovoltaic cells -- Materials; Solar cells -- Materials; Electronic books